2008
DOI: 10.1111/j.1743-6109.2008.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin, Subjective Well-Being and Sexual Dysfunction: An Open Label Observational Study Comparing Quetiapine with Risperidone

Abstract: Introduction Sexual dysfunction is a frequent side effect of antipsychotic treatment. Increased prolactin levels are believed to be responsible for this sexual impairment despite contradictory results. Aim The primary objective of the present study was to examine the relationship between sexual dysfunction, subjective well-being and prolactin levels in patients with schizophrenia treated either with risperidone or quetiapine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
1
23
0
2
Order By: Relevance
“…Although it is often suggested that increased PRL levels are responsible for sexual dysfunctions in schizophrenic patients, one is struck by the fact that the literature on this topic is limited [128, 428] and that the evidence is contradictory and inconclusive [128, 129, 429, 430]. Some studies have shown an association between sexual side effects and PRL elevation, while others have failed to support this [431].…”
Section: Consequences Of Hprlmentioning
confidence: 99%
“…Although it is often suggested that increased PRL levels are responsible for sexual dysfunctions in schizophrenic patients, one is struck by the fact that the literature on this topic is limited [128, 428] and that the evidence is contradictory and inconclusive [128, 129, 429, 430]. Some studies have shown an association between sexual side effects and PRL elevation, while others have failed to support this [431].…”
Section: Consequences Of Hprlmentioning
confidence: 99%
“…This may well be explained by a considerably smaller sample studied by this group. Westheide and colleagues 47 found an association between SD and subjective well-being in risperidone-treated patients, emphasizing the clinical relevance of sexual functioning in schizophrenia and its potential influence on compliance behavior, as also discussed by Montejo et al 15 In summary, our findings indicate that SD in first-episode schizophrenia patients is a common problem, as shown by its prevalence and chronicity. These adverse events were fairly evenly distributed between the 5 antipsychotics administered while patients on amisulpride presented with a clearly higher risk for amenorrhea and galactorrhea.…”
Section: Discussionmentioning
confidence: 57%
“…Сходные результаты о влиянии ГАН на сексуальную функцию у женщин были получены S. Smith [21] в отно- Журнал неврологии и психиатрии, 11,2016 шении снижения полового влечения и дефицита влага-лищной смазки, H. Knegtering [18] -трудности в дости-жении оргазма, M. Rettenbacher [19] -ослабления поло-вого влечения и трудности в достижении оргазма. Данные об ассоциации ГАН у мужчин со снижением полового влечения и нарушением эрекции совпадают с данными ряда других исследователей [20,23,25,31]. Представленная в данной статье информация может быть полезной как для практикующих эндокринологов, так и психиатров в отношении возможности своевремен-но диагностировать ГАН.…”
Section: Discussionunclassified
“…[24], кото-рые выявили значимую положительную ассоциацию меж-ду уровнем пролактина и суммарным баллом Аризонской шкалы сексуального опыта (ASEX), а также рядом суб-шкал ASEX (сила полового влечения, сексуальное воз-буждение, эректильная функция). В ряде работ [10,[24][25][26][27][28] у пациентов, получавших рисперидон, оланзапин, арипипразол, галоперидол, кветиапин, связь между ГАН и сексуальными нарушениями не была выявлена.…”
unclassified